NILAI MORAL DALAM NOVEL A UNTUK AMANDA KARYA ANNISA IHSANI SEBAGAI PEMBENTUK KARAKTER BAGI PESERTA DIDIK SMA MELALUI PEMBELAJARAN SASTRA - Vio Amandini Afriliana; Nazla Maharani Umaya; Pipit Mugi Handayani (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
This study uses literature as a research object, which contains all kinds of social phenomena in it. The purpose of this study is to describe the moral values ​​contained in the novel A for Amanda by Annisa Ihsani and to describe the moral values ​​in the novel A for Amanda by Annisa Ihsani as teaching material for class XI high school students. This study used a qualitative approach with data collection techniques, observing and noting. From this research, it was found that there are forms of moral values ​​in novel A for Amanda, namely 1) forms of moral values ​​of human relations with God, 2) forms of moral values ​​of human relations with oneself, 3) forms of moral values ​​of human relations with other humans in the social sphere and the natural environment. The form of moral values ​​is utilized in the content of teaching materials contained in KD 3.11 analyzing messages from a read fiction book. The conclusions obtained by Novel A for Amanda can be used as teaching materials for basic competency 3.11. analyze the message of a fiction book read.